The development of sensor network for structural health monitoring using CANopen protocal - W. Punurai (2018)
This paper presents the design and construction of a measurement system to be used in SHM applications. The proposed system is developed based on the concept of sensoring network using CANopen protocol and is composed of three modules; sensor node module (a set of embedded system boards equipped with strain gauges attached to the desired locations on the structure), a database server module which collects measured data from every sensor node in real-time, and a computer running on internet-based client software. The three modules are connected through CAN data bus which operates at baud rate of 1 Mb/s with the maximum bus length of 50 m. The system was tested to measure signals from a series of strain gauges bonded to steel, concrete and steel-plate strengthened concrete beams subjected to load tests. At a 100 Hz sampling rate and for use with a fundamental frequency of 2-5 Hz, it was shown that the system was more tolerant to the effect of noise and signal distortion when compared to conventional analog data loggers. The strain values obtained from the system were in good agreement with values obtained from a TDS-302 commercial data logger, with a small percentage of error of less than 5%.